Optimal H2 output-feedback control of sampled-data systems. Issue 9 (1st September 2020) - Amorim, Matheus F.; Gonçalves, Alim P. C.; Fioravanti, André R.; Souza, Matheus
ABSTRACT: This paper addresses the output feedback control design problem with limited data-rate constraints. These communication constraints may affect the transmission of control signals or measurements, giving rise to different models, depending on the interconnection architecture. The closed-loop system composed by plant and controller can be modelled as a Hybrid System whose stability and H 2 performance can be determined in terms of necessary and sufficient Linear Matrix Inequalities. However, for the design of the appropriate feedback gains, those conditions become non-convex and we propose an approach to obtain satisfactory solutions. Numerical examples are included.